An Integrated Perspective : The Impact of Digital Financial Knowledge and Self-Esteem on Financial Behavior in the Lives of College Students - Azaria, Candra; Susilaningsih, Susilaningsih; Sudarno, Sudarno (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to analyze the impact of digital financial knowledge on college students’ financial behavior, and the involvement of self-esteem as a mediator variable. This study used a quantitative survey method. The sample used was a group of 249 undergraduate students majoring in accounting education at Universitas Sebelas Maret and Universitas Negeri Semarang. A conceptual model, containing hypotheses outlining the impact was constructed and assessed through validity, reliability, frequency statistics and path analysis. The findings indicated a direct and positive correlation of digital financial knowledge on financial behavior. This research contributes fresh perspectives by providing both practical and theoretical insights into the variables employed in the study.